Assessment of Patient Satisfaction Towards Ophthalmology Services in a Tertiary Care Hospital: A Cross-sectional Study - Shrestha, Ram; Rajkarnikar, Sagar; Thapa, Kamala; Khanal Rijal, Roshija; Kausar, Neyaz; Khadka, Sitaram (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: The quality of medical care directly affects patient satisfaction. The delicate nature of eye care and its potential impact on patients’ well-being necessitates the assessment of patient satisfaction towards ophthalmology services. This study was conducted to evaluate the patient satisfaction towards ophthalmology services. Methods: A hospital based cross-sectional study was conducted among 384 patients visiting Ophthalmology Department of Shree Birendra Hospital. Descriptive statistics was used to present the demographic details of the participants. Normality of the data was checked by Shapiro-Wilk test. Results: The response rate of participants was 98.46%. Out of 384 respondents, 214 patients were satisfied with the healthcare they received. The satisfaction level was 55.7% (95% CI: 51.0-60.4). Conclusions: The patient satisfaction towards ophthalmology services was found satisfactory. However, there are various aspects which need to be improved for enhancing quality service for the better healthcare facility.